1975
DOI: 10.1111/j.1600-0773.1975.tb03329.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of metoprolol‐(3H) in man, the dog and the rat

Abstract: The main urinary metabolites of metoprolol‐(3H) in man, the dog and the rat were identified by gas chromatography and mass spectrometry by comparison with synthesized reference compounds. The amounts of the different metabolites in urine were determined by radio‐gas chromatography. In man metoprolol was metabolized by oxidative deamination, O‐dealkylation with subsequent oxidation and aliphatic hydroxylation into three main urinary metabolites which together accounted for 85% of the total urinary excretion. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(45 citation statements)
references
References 6 publications
4
37
0
4
Order By: Relevance
“…The fragment ions of M6 at m/z 252, 228, and 193 were also 16 Da higher than the fragment ions of M1 at m/z 236, 212, and 177, respectively, which suggested that M6 was a hydroxyl metabolite of M1. Similar metabolic pathways also exist in humans, dogs, horses, and rats [2,3] . For M7, the protonated molecule ([M+H] + ) was at m/z 416, and 162 Da higher than that of M1.…”
Section: Metabolite M2 the Retention Time Of M2 ([M+h]mentioning
confidence: 70%
“…The fragment ions of M6 at m/z 252, 228, and 193 were also 16 Da higher than the fragment ions of M1 at m/z 236, 212, and 177, respectively, which suggested that M6 was a hydroxyl metabolite of M1. Similar metabolic pathways also exist in humans, dogs, horses, and rats [2,3] . For M7, the protonated molecule ([M+H] + ) was at m/z 416, and 162 Da higher than that of M1.…”
Section: Metabolite M2 the Retention Time Of M2 ([M+h]mentioning
confidence: 70%
“…The pellets containing the microsomes were resuspended in 0.1 M Tris (pH 7.4), 20% glycerol, and 0.15 M NaCl, and the microsomes obtained from each dose group were pooled. A protein (Borg et al, 1975a;Boralli et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…pretreatment). To obtain the complete absorption and metabolic profile of metoprolol, the plasma levels of three major circulating metabolites of metoprolol [a-hydroxy-metoprolol (OHM), O-desmethyl-metoprolol (ODM), and metoprolol acid (MA) (Borg et al, 1975a)] were also measured. In addition, to put into perspective the impact of ABT on metoprolol intestinal and hepatic metabolism, in vitro metabolic studies using intestinal and hepatic microsomes prepared from ABT pretreated rats were conducted.…”
mentioning
confidence: 99%
“…Apesar da completa absorção gastrintestinal, em razão da alta eliminação pré-sistêmica somente 50% da dose atinge a circulação sob a forma inalterada (BORG et al, 1975;LEEMANN;DEVI;DAYER, 1993) A formação do metabólito α-hidroximetoprolol é dependente da atividade geneticamente determinada do CYP2D6 e relaciona-se com o fenótipo de oxidação tipo debrisoquina/esparteína (LENNARD; TUCKER; WOODS, 1986).…”
Section: Lista De Figurasunclassified
“…A via quantitativamente mais importante é a oxidação do produto da Odesmetilação resultando na formação do ácido O-desmetilmetoprolóico, e corresponde a eliminação de 65% da dose em humanos (BORG et al, 1975). A exposição experimental a vapores de solventes pode ser realizada em câmaras de dois tipos: as que expõem todo o animal e aquelas em que a exposição se dá apenas pelo nariz (NOES -Nose Only Exposure System).…”
Section: Lista De Figurasunclassified